Hubungan Pengetahuan dan Perilaku Makan dengan Kenaikan Berat Badan Ibu selama Periode Kehamilan di Wilayah Kerja Puskesmas Kota Atambua - Alberth M. Bau Mali (Kupang Journal of Food and Nutrition Research, 2022)
ABSTRACT Background : Pregnant women are one of the groups most prone to nutritional problems. Nutritional problems experienced by pregnant women before or during pregnancy can affect the growth of the fetus that is being conceived. One of the reasons for the inhibition of fetal growth is poor maternal nutrition, marked by low maternal weight gain or pre-pregnancy weight gain. Therefore, good preparation is needed so that the quality of the baby born is also good (Khomsan 2002) Research Objectives: This study aims to describe the relationship between knowledge and eating behavior with changes in maternal weight during the pregnancy period at the Atambua Public Health Center. Methods: This research is a descriptive study with a cross sectional method in which the research subjects are pregnant women in the third trimester, data is obtained through direct interviews with pregnant women, while secondary data is obtained from the profile of the public health center, mother cohort registers, KMS pregnant women, PWS KIA. Descriptive data analysis was carried out on the variable knowledge of pregnant women nutrition, maternal eating behavior during the pregnancy period, the increase in maternal weight during the pregnancy period, while the analytic analysis used the chi-square statistical test. Results: There is a relationship between the knowledge of pregnant women and the weight gain of pregnant women at the Atambua Public Health Center. The results of these studies indicate that the higher the knowledge of pregnant women about nutrition is followed by the increase in maternal weight gain during pregnancy. There is a relationship between the eating behavior of pregnant women and the weight gain of pregnant women at the Atambua Public Health Center. The results of this study indicate that the more positive the mother's eating behavior during the pregnancy period will be followed by an increase in the mother's weight gain during pregnancy. Keywords: pregnant women, knowledge, eating behavior